Ang batang natutong maging matapang (The child who learned to be brave) - Villanueva, Rene O. (Lampara books, 2007)
"While Noynoy's father is away, the tamuninis visit their house and take his mother and his baby brother away. Noynoy knows that once his mother and brother Paco reach the town of Bumburiki, he will never be able to get them back from the tamuninis. His father will never forgive him because he failed to keep watch over his mother and brother. Grandfather Uban tells the story of a boy whose mother and brother are snatched by spirits learns how to be brave."